Method of forming inorganic oxide coating on monolith article

By spraying aluminosilicate zeolite inorganic particles and silicone resin on the porous ceramic filter, forming a coating and calcining treatment, the problem of insufficient water resistance and adhesion of porous ceramic filters in the prior art is solved, and higher water resistance and filtration efficiency are achieved.

CN119730960APending Publication Date: 2025-03-28JOHNSON MATTHEY PLC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380060131.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-12
Filing Date
2023-08-22
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing porous ceramic filters have problems of insufficient water resistance and adhesion when treating exhaust gas, resulting in reduced filtration efficiency and easy accumulation of particulate cakes.

Method used

Sprayed inorganic particles and silicone resins are used as dry-particle aerosols to form a coating, and the water resistance and thermal stability of the monolithic products are enhanced by calcination.

Benefits of technology

It significantly improves the water resistance and filtration efficiency of monolith products, and enhances its thermal stability, and is suitable for treating exhaust gases, especially vehicle exhaust gases.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005273673640000171
    Figure BDA0005273673640000171
Patent Text Reader

Abstract

A method of forming an inorganic oxide coating on a monolith article is disclosed. The coated monolith article is suitable for treating exhaust gases. The method includes spraying inorganic particles comprising an aluminosilicate zeolite having an SAR greater than 100: 1 and a silicone resin as a dry particulate aerosol to form a coating. An uncalcined porous monolith article for forming a monolith article for treating exhaust gases is also provided. The uncalcined monolith article comprises a dry particulate composition comprising inorganic particles and a silicone resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for forming an inorganic oxide coating on a monolithic article. In particular, the coated monolithic article is suitable for treating exhaust gases. More particularly, the method comprises spraying inorganic particles and a silicone resin as a dry particulate aerosol to form a coating. The present invention also relates to an uncalcined porous monolithic article for forming a monolithic article for treating exhaust gases. In particular, the uncalcined monolithic article comprises a dry particulate composition comprising inorganic particles and a silicone resin. Background Art

[0002] There are issues regarding the emission of particulate matter (PM), commonly referred to as soot, from internal combustion engines, especially diesel and gasoline engines in automotive applications. The main issues are associated with potential health effects, particularly with very small particles with sizes in the nanometer range.

[0003] Diesel particulate filters (DPF) and gasoline particulate filters (GPF) have been manufactured using a variety of materials (including sintered metals, ceramics or metal fibers, etc.), of which the most common type in actual large-scale production is a wall-flow type made of a porous ceramic material, which is manufactured in the form of a monolithic array of many small channels extending along the length of the body. The alternating channels are blocked at one end, so the exhaust gas is forced to pass through the porous ceramic channel wall, which prevents most of the particles from passing through, so only the filtered gas enters the environment. Ceramic wall-flow filters in commercial production include those made of cordierite, various forms of silicon carbide and aluminum titanate. The actual shape and size of the practical filter on the vehicle and characteristics such as the thickness of the channel wall and its porosity depend on the application of interest. The average size of the pores in the filter channel wall of the ceramic wall-flow filter through which the gas passes is typically in the range of 5μm to 50μm and is typically about 20μm. In stark contrast, most diesel particulate matter from modern passenger car high speed diesel engines is much smaller in size, for example 10 nm to 200 nm.

[0004] Some PM may remain within the pore structure in the filter wall, and this can gradually accumulate in some applications until the pores are bridged by a network of PM, and this PM network then enables easy formation of a particle cake on the inner walls of the filter channels. The particle cake is an excellent filter medium, and its presence provides very high filtration efficiency. In some applications, the soot is continuously burned on the filter as it is deposited, which prevents the particle cake from accumulating on the filter.

[0005] For some filters, such as light-duty diesel particulate filters, it is necessary to periodically remove trapped PM from the filter to prevent the buildup of excessive back pressure, which is detrimental to engine performance and can result in poor fuel economy. Therefore, in diesel applications, retained PM is removed from the filter by burning it in the air in a process during which the amount of available air and the amount of excess fuel used to reach the high temperatures required to ignite the retained PM are very carefully controlled. Towards the end of this process, which is generally referred to as regeneration, the removal of the last remaining particles in the filter can result in a significant reduction in filtration efficiency and the release of a burst of many small particles into the environment. As a result, the filter may have low filtration efficiency when first used and subsequently after each regeneration event and also during the latter part of each regeneration process.

[0006] Thus, it is desirable to improve and / or maintain filtration efficiency at all times—eg, during the early life of a filter when it is first used, and / or during and immediately after regeneration, and / or when the filter is loaded with soot.

[0007] WO 2011 / 151711 (the entire contents of which are incorporated herein by reference) describes a method of making a filter for filtering particulate matter from exhaust gases emitted by a lean-burn internal combustion engine. The filter comprises a porous substrate having an inlet surface and an outlet surface, wherein the inlet surface is separated from the outlet surface by a porous structure containing pores of a first average pore size. The inlet surface comprises a bridging network comprising interconnected refractory material particles on the pores of the porous structure. The method comprises the step of contacting the inlet surface of the filter substrate with an aerosol comprising a refractory material in dry powder form.

[0008] WO 2021 / 028692 (the entire contents of which are incorporated herein by reference) describes a vehicle exhaust filter comprising a porous substrate having an inlet face and an outlet face, the porous substrate comprising an inlet channel extending from the inlet face and an outlet channel extending from the outlet face; the inlet channel and the outlet channel are separated by a plurality of filter walls having a porous structure; the vehicle exhaust filter is loaded with a refractory powder, the refractory powder having a tap density of less than 0.10 g / cm before loading 3 ; The vehicle exhaust filter has a mass loading of refractory powder of less than 10 g / L; and wherein greater than 40% of the refractory powder is located within the porous structure of the plurality of filter walls, and less than 60% of the refractory powder is coated on the outer surface of the plurality of filter walls. WO 2021 / 028692 also describes suitable methods and apparatus for spraying dry refractory powders, such as dry particulate aerosols, onto channels of a porous substrate, preferably wherein greater than 50% of the refractory powder, optionally up to 100% of the refractory powder may be located with the porous structure of the plurality of filter walls.

[0009] WO 2020 / 047708 discloses articles including porous bodies such as porous ceramic honeycombs, and methods for making such articles and porous bodies, the porous bodies including a material such as a filter material, for example a porous inorganic layer disposed on at least a portion of the porous body. The method comprises contacting an inorganic material in a suspension, which may be water-based or organic-based, for example an alcohol such as ethanol or methanol, with a gaseous carrier liquid.

[0010] The present inventors have found that porous filter substrates treated with refractory powder materials such as those described in WO 2021 / 028692 have poor water resistance and adhesion. A porous filter substrate treated with Alu 130) fails to provide the water resistance required for use under certain engine conditions, particularly during continuous engine cold starts. As mentioned above, for example, for heavy duty diesel (HDD) catalyzed soot filter (CSF) applications, the filter must be able to withstand several ash cleaning cycles.

[0011] The present invention provides an improved method for producing more efficient coated monolithic articles that advantageously exhibit higher water resistance, improved filtration efficiency, and improved thermal stability. Summary of the invention

[0012] According to a first aspect of the present invention, there is provided a method for forming an inorganic oxide coating on a monolithic article for treating exhaust gas, the method comprising:

[0013] providing a porous monolithic article comprising a plurality of channels for passage of exhaust gas, each channel having a gas contacting surface;

[0014] spraying inorganic particles comprising an aluminosilicate zeolite having a silica to alumina molar ratio (SAR) greater than 100:1 and a silicone resin as a dry particulate aerosol onto a gas contacting surface to form a coating; and

[0015] The coating is calcined to provide a coated monolithic article.

[0016] In a further aspect, there is provided an uncalcined porous monolithic article for forming a monolithic article for treating exhaust gas, the monolithic article being obtainable by a method comprising the steps of:

[0017] providing a porous monolithic article comprising a plurality of channels for passage of exhaust gas, each channel having a gas contacting surface;

[0018] Inorganic particles having a SAR greater than 100:1 and a silicone resin are sprayed onto the gas contacting surface as a dry particulate aerosol to form a coating.

[0019] In another aspect, there is provided a coated monolithic article for treating exhaust gases obtainable by a method as described herein with respect to the first aspect. The coated monolithic article has enhanced water resistance and thermal stability over known coated monolithic articles, and as described herein, the article is preferably a catalytic article and / or a wall flow filter. Such an article is particularly suitable for treating exhaust gases, particularly vehicle exhaust gases. The inventors have found that the highly cross-linked silica present in the coated monolithic article is highly effective in bonding inorganic particles comprising an aluminosilicate zeolite having a SAR greater than 100:1 to the gas contacting surfaces of the channels of the porous monolithic article, and that the presence of the aluminosilicate zeolite having a SAR greater than 100:1 imparts improved thermal stability to the coated monolithic article.

[0020] In further aspects of the present invention, a vehicle exhaust system including the coated monolithic article is provided. DETAILED DESCRIPTION

[0021] According to a first aspect of the present invention, there is provided a method for forming an inorganic oxide coating on a monolithic article for treating exhaust gas, the method comprising:

[0022] providing a porous monolithic article comprising a plurality of channels for passage of exhaust gas, each channel having a gas contacting surface;

[0023] spraying inorganic particles having a SAR greater than 100:1 and a silicone resin as a dry particulate aerosol onto a gas contacting surface to form a coating; and

[0024] The coating is calcined to provide a coated monolithic article.

[0025] The present disclosure will now be further described. In the following paragraphs, different aspects / embodiments of the present disclosure are defined in more detail. Unless there is a clear contrary description, each aspect / embodiment so defined may be combined with any other aspect / embodiment or multiple aspects / embodiments. In particular, any feature indicated as being preferred or advantageous may be combined with any other one or more features indicated as being preferred or advantageous.

[0026] The method of the present invention forms an inorganic oxide coating on a monolithic article, thereby forming a coated monolithic article. The monolithic article having the inorganic oxide coating is suitable for treating exhaust gas. The exhaust gas may be lean burn exhaust gas preferably from a vehicle engine, and the exhaust gas is treated by passing the exhaust gas through the channels of the monolithic article so that the exhaust gas contacts the gas contact surfaces of the plurality of channels.

[0027] The method includes providing a porous monolithic article comprising a plurality of channels for passage of exhaust gas, each channel having a gas contact surface. Porous monolithic articles are well known in the art. Porous monolithic articles may sometimes be referred to as substrates, preferably honeycomb substrates, preferably ceramic honeycomb substrates. Such substrates include a plurality of channels suitable for passage of exhaust gas. The channels are parallel and extend from an inlet end (or first end) to an outlet end (or second end), i.e., the channels extend axially through the article. Typically, the channels have a square cross-section, but any known monolithic design may be used.

[0028] The porous monolithic article / substrate may be formed, for example, from sintered metals, ceramics, or metal fibers, etc. For example, the article may be formed from cordierite, various forms of silicon carbide, or aluminum titanate.

[0029] In some embodiments, the monolithic article is a monolithic filter. It is particularly preferred that the monolithic filter is a wall-flow filter (also referred to as a wall-flow monolithic article). Wall-flow filters are well known, and typically, adjacent channels are alternately blocked at each end of the monolithic article so that, in use, exhaust gases pass along the inlet channel (i.e., the channel that opens at the inlet end of the monolithic article for receiving exhaust gases) and are forced through the channel wall into the adjacent outlet channel (i.e., the channel that opens at the outlet end of the monolithic article).

[0030] The channel walls have a pore distribution that provides the desired porosity for the monolithic article, with the average size of the pores in the channel walls (e.g., filter walls) typically being in the range of 5 μm to 50 μm. Each channel has a gas contact surface. That is, each channel has a surface suitable for contacting exhaust gas, for example, when in use. The surface may be provided by the channel wall surface and / or the pores contained therein.

[0031] In another particularly preferred embodiment, the porous monolith article is a catalyst article (i.e., a catalytic filter). Catalytic porous monolith articles are well known and exhibit properties such as oxidation, NO x The porous monolithic article may include one or more washcoats, preferably catalytic washcoats. Washcoats are compositions that coat and penetrate the porous structure of the article. The article including the one or more washcoats is then preferably calcined before the inorganic particles and the silicone resin are sprayed onto the channels as described herein. Thus, the catalyst article may be selected from, for example, a three-way catalyst (TWC), a NO x Adsorbents, oxidation catalysts, selective reduction catalysts (SCR), hydrocarbon traps and lean NO x Catalyst. The catalyst article may contain one or more platinum group metals, particularly those selected from the group consisting of platinum, palladium and rhodium.

[0032] In another particularly preferred embodiment, the porous monolithic article is a catalyzed wall flow filter. Thus, the article can be, for example, a catalyzed soot filter (CSF), a selective catalytic reduction filter (SCRF), a lean NO x a trap filter (LNTF), a gasoline particulate filter (GPF), an ammonia slip catalyst filter (ASCF), or a combination of two or more thereof (eg, a filter including a selective catalytic reduction (SCR) catalyst and an ammonia slip catalyst (ASC)).

[0033] In another particularly preferred embodiment, the porous monolithic article is a gasoline particulate filter, which is a catalyzed wall flow filter comprising a TWC catalyst. Generally speaking, the gasoline particulate filter comprises: a platinum group metal selected from the group consisting of Pt, Pd, Rh and mixtures thereof; an oxygen storage capacity (OSC) material; and optionally an inorganic support material.

[0034] The shape and size of the filter (e.g., characteristics such as channel wall thickness and its porosity) can vary depending on the intended application of the filter. The filter can be configured for use with an internal combustion engine to filter exhaust gases emitted by the internal combustion engine. The internal combustion engine can be a gasoline spark ignition engine. However, the filter has specific applications when configured for use with an internal combustion engine in the form of a diesel or gasoline engine.

[0035] The wall-flow filter may be an asymmetric wall-flow filter. Asymmetric wall-flow filter designs are known, for example, from WO2005 / 030365, which discloses a honeycomb filter comprising an array of interconnected porous walls defining an array of first and second channels. The first channel is bounded on its side by the second channel and has a larger hydraulic diameter than the second channel. The first channel has a square cross-section, wherein the corners of the first channel have a shape such that the thickness of the porous wall adjacent to the corner of the first channel is comparable to the thickness of the porous wall adjacent to the edge of the first channel and the second channel. In use, the first channel having the larger hydraulic diameter is oriented to the upstream side. The Society of Automotive Engineers SAE Technical Paper Series 2007-01-0656 explains: "Due to the contraction and expansion of the gas at the inlet and outlet of the filter channels, there is a pressure drop loss in the clean state for the ACT design [for catalytic asymmetric channel technology (ACT) wall-flow filters]. However, when operating on a vehicle, the filter is in a completely clean (fully regenerated) state for very little time." WO2005 / 030365 also explains that the advantages of the asymmetric filter design include an increased effective surface area available for collecting soot and ash particles in the inlet portion of the honeycomb filter, thereby increasing the total storage capacity of the honeycomb filter. The general common sense textbook "Catalytic Air Pollution Control—Commercial Technology", 3rd edition, Ronald M. Heck et al., John Wiley & Co., Hoboken, NJ, USA (2009) pp. 338-340 explains: "This type of [asymmetric filter] channel design achieves a combination of higher ash storage capacity and lower ash loading back pressure due to the larger hydraulic diameter and higher open volume at the inlet. The ACT design also helps to maintain the mechanical and thermal durability of the filter.

[0036] The method also includes spraying inorganic particles comprising an aluminosilicate zeolite having a SAR greater than 100:1 and a silicone resin as a dry particulate aerosol onto the gas contact surface to form a coating. Thus, the method includes spraying a dry powder (i.e., dry particles) suspended in a gas (i.e., as an aerosol) onto the gas contact surface of a plurality of channels on the monolithic article. Spraying dry powders onto monolithic articles is known in the art. Suitable methods and apparatus are described, for example, in WO 2011 / 151711 and WO 2021 / 028692.

[0037] The present inventors have discovered that by combining inorganic particles comprising an aluminosilicate zeolite having a SAR greater than 100:1 with a silicone resin in a dry powder used to form a dry particle aerosol, the resulting article exhibits significantly improved water resistance, improved adhesion of the inorganic particles to the channel wall surfaces, and improved thermal stability of the coated monolithic article.

[0038] One advantage of the present invention is that the coated monolithic article, such as a filter containing a catalyst in the filter wall, can be processed after the catalyst is supported on the filter and such that the inorganic coating does not interfere with the catalyst in and / or on the filter wall. In addition, the inventors have discovered that the silicone resin as described herein does not require high temperature processing that may be detrimental to the catalyst, and the silicone resin enables the inorganic particles to be more effectively retained and adhered to the article channels. The presence of the aluminosilicate zeolite having a SAR greater than 100:1 improves the thermal stability of the coated monolithic article.

[0039] Silicone resins are known and are branched cage-like oligosiloxanes and polysiloxanes. The branching in silicone resins is due to the presence of so-called "T" and / or "Q" units in the resin, which refer to RSiO3 and SiO4 units (R is alkyl or aryl), respectively, in which the additional silicon unit is bonded to an oxygen atom. The "M" unit (i.e., R3SiO2 unit) is a terminal unit in which the oxygen atom provides the connection to the resin backbone. Similarly, the "D" unit (i.e., R2SiO2 unit) provides a linear connection across two oxygen atoms. A well-known unbranched and linear polysiloxane is polydimethylsiloxane (PDMS; i.e., (Me2SiO) n ).

[0040] As will be appreciated, this requirement of spraying the inorganic particles and the silicone resin as a dry particulate aerosol requires that the silicone resin is a solid particulate. Therefore, the silicone resin may be referred to herein as silicone resin particles. Preferably, the silicone resin is solid at room temperature (e.g., about 25°C). Therefore, the silicone resin preferably has a melting point greater than 25°C, preferably greater than 30°C, more preferably greater than 35°C. Preferably, the melting point of the silicone resin is less than 100°C, preferably less than 95°C, less than 90°C, less than 85°C or less than 80°C. Unbranched polysiloxanes such as PDMS generally have lower melting points than branched silicone resins. For example, the melting point of PDMS is about -40°C. WO 2011 / 151711 discloses bonding the powder in place by treatment with polydimethylsiloxane, which forms silica when hydrolyzed at sufficiently high temperatures.

[0041] Similarly, the inventors have found that it may be preferred that the silicone resin has a glass transition temperature (Tg) greater than 30° C., preferably greater than 35° C., and / or less than 100° C., preferably less than 80° C. Without wishing to be bound by theory, the inventors believe that silicone resins having such melting points and / or glass transition temperatures are particularly suitable for powder coating processes, i.e., for effective dispersion of microparticles along with inorganic particles on a monolithic article, but the melting points and / or glass transition temperatures are low enough to allow low temperature calcination to effectively and efficiently adhere the inorganic particles to the gas contacting surfaces of the channel walls.

[0042] The inorganic particles comprise an aluminosilicate zeolite having a SAR (SAR) greater than 100: 1. The aluminosilicate zeolite preferably has a SAR greater than 200: 1, more preferably greater than 300: 1, even more preferably greater than 400: 1, and most preferably greater than 500: 1. In some embodiments, the aluminosilicate zeolite has a SAR greater than 1000: 1.

[0043] The aluminosilicate zeolites having a SAR greater than 100: 1 can have a framework type selected from the group consisting of ABW, ACO, AEI, AEL, AEN, AET, AFG, AFI, AFN, AFO, AFR, AFS, AFT, AFX, AFY, AHT, ANA, APC, APD, AST, ASV, ATN, ATO, ATS, ATT, ATV, AVL, AWO, AWW, BCT, BEA, BEC, BIK, BOG, BPH, BRE, CAN, CA S, SCO, CFI, SGF, CGS, CHA, CHI, CLO, CON, CZP, DAC, DDR, DFO, DFT, DOH, DON, EAB, EDI, EEI, EMT, EON, EPI, ERI, ES V, ETR, EUO, FAU, FER, FRA, GIS, GIU, GME, GON, GOO, HEU, IFR, IFY, IHW, IRN, ISV, ITE, ITH, ITW, IWR, IWW, JBW, KF I, LAU, LEV, LIO, LIT, LOS, LOV, LTA, LTL, LTN, MAR, MAZ, MEI, MEL, MEP, MER, MFI, MFS, MON, MOR, MOZ, MSO, MTF, MT N, MTT, MTW, MWF, MWW, NAB, NAT, NES, NON, NPO, NPT, NSI, OBW, OFF, OSI, OSO, OWE, PAR, PAU, PHI, PON, RHO, RON, RR O, RSN, RTE, RTH, RUT, RWR, RWY, SAO, SAS, SAT, SAV, SBE, SBS, SBT, SFE, SFF, SFG, SFH, SFN, SFO, SFW, SGT, SOD, SO S, SSY, STF, STI, STT, TER, THO, TON, TSC, UEI, UFI, UOZ, USI, UTL, VET, WI, VNI, VSV, WIE, WEN, YUG, ZON, or combinations thereof. In some embodiments, the aluminosilicate zeolite having a SAR greater than 100: 1 may have a framework type selected from the group consisting of AEI, AFT, AFV, AFX, AVL, BEA, CHA, DDR, EAB, EEI, ERI, FAU, FER, IFY, IRN, KFI, LEV, LTA, LTN, MER, MOR, MWF, MFI, NPT, PAU, RHO, RIE, RTH, SAS, SAT, SAV, SFW, TSC, and UFI. In some embodiments, the aluminosilicate zeolite having a SAR greater than 100: 1 may have a framework type selected from the group consisting of AEI, BEA, CHA, and MFI.In some embodiments, the aluminosilicate zeolites having a SAR greater than 100: 1 have a BEA framework type. In some embodiments, the aluminosilicate zeolites having a SAR greater than 100: 1 have a MFI framework type.

[0044] In addition to the aluminosilicate zeolite having a SAR greater than 100: 1, the inorganic particles may include a second zeolite material. Examples of suitable second zeolite materials include silicate zeolites, aluminosilicate zeolites, metal-substituted aluminosilicate zeolites, AlPO, MeAlPO, SAPO, MeAPSO, and the like. The second zeolite material may have a framework type selected from the group consisting of ABW, ACO, AEI, AEL, AEN, AET, AFG, AFI, AFN, AFO, AFR, AFS, AFT, AFX, AFY, AHT, ANA, APC, APD, AST, ASV, ATN, ATO, ATS, ATT, ATV, AVL, AWO, AWW, BCT, BEA, BEC, BIK, BOG, BPH, BRE, CAN, CAS, SCO, CFI, S GF, CGS, CHA, CHI, CLO, CON, CZP, DAC, DDR, DFO, DFT, DOH, DON, EAB, EDI, EEI, EMT, EON, EPI, ERI, ESV, ETR, EUO , FAU, FER, FRA, GIS, GIU, GME, GON, GOO, HEU, IFR, IFY, IHW, IRN, ISV, ITE, ITH, ITW, IWR, IWW, JBW, KFI, LAU, L EV, LIO, LIT, LOS, LOV, LTA, LTL, LTN, MAR, MAZ, MEI, MEL, MEP, MER, MFI, MFS, MON, MOR, MOZ, MSO, MTF, MTN, MTT , MTW, MWF, MWW, NAB, NAT, NES, NON, NPO, NPT, NSI, OBW, OFF, OSI, OSO, OWE, PAR, PAU, PHI, PON, RHO, RON, RRO, R SN, RTE, RTH, RUT, RWR, RWY, SAO, SAS, SAT, SAV, SBE, SBS, SBT, SFE, SFF, SFG, SFH, SFN, SFO, SFW, SGT, SOD, SOS , SSY, STF, STI, STT, TER, THO, TON, TSC, UEI, UFI, UOZ, USI, UTL, VET, WI, VNI, VSV, WIE, WEN, YUG, ZON, or their combination.

[0045] The inorganic particles may include refractory oxide particles, which may be based on an oxide selected from the group consisting of: alumina, silica, zirconia, ceria, chromia, magnesia, calcium oxide, titania, and mixed oxides of any two or more thereof. Preferably, the refractory oxide particles include calcium aluminate, fumed alumina, fumed silica, fumed titania, fumed zirconia, fumed ceria, alumina aerogel, silica aerogel, titania aerogel, zirconia aerogel, ceria aerogel or mixtures thereof. The one or more refractory powders (refractory oxide particles) may be produced by a pyrometallurgical process, such as flame pyrolysis.

[0046] The amount of aluminosilicate zeolite with a SAR greater than 100: 1 present in the inorganic particles can be 10% to 99% by weight, preferably 50% to 99% by weight, more preferably 80% to 99% by weight, and most preferably 90% to 99% by weight. In some embodiments, the inorganic particles consist of aluminosilicate zeolites with a SAR greater than 100: 1. In some embodiments, the inorganic particles consist of aluminosilicate zeolites with a SAR greater than 100: 1. In some embodiments, the inorganic particles consist of aluminosilicate zeolites with a SAR greater than 200: 1. In some embodiments, the inorganic particles consist of aluminosilicate zeolites with a SAR greater than 300: 1. In some embodiments, the inorganic particles consist of aluminosilicate zeolites with a SAR greater than 400: 1. In some embodiments, the inorganic particles consist of aluminosilicate zeolites with a SAR greater than 500: 1. In some embodiments, the inorganic particles consist of aluminosilicate zeolites with a SAR greater than 1000: 1.

[0047] Preferably, the inorganic particles and / or silicone resin particles have a d value greater than 0.2 μm, preferably greater than 0.5 μm, and / or less than 50 μm, preferably less than 25 μm, preferably less than 20 μm, preferably less than 15 μm, preferably less than 10 μm by volume. 50 .

[0048] Preferably, the dry particle aerosol has a tap density of less than 1.5 g / cm 3 The dry particle composition is formed. The dry particle composition can be referred to as dry particle powder. The dry particle composition is preferably composed of inorganic particles and / or silicone resin. In some preferred embodiments, the inorganic particles have a particle size of less than 0.1 g / cm 3 (usually for fumed refractory oxides) of tap density. In other preferred embodiments, the inorganic particles have a tap density greater than 0.1 g / cm 3 , preferably greater than 0.2 g / cm 3 For example, zeolite particles such as Cu-substituted zeolites may preferably have a tap density of about 0.25 g / cm3 In other preferred embodiments, inorganic particles such as refractory oxide particles may have a tap density of less than 1.4 g / cm 3 , preferably less than 1.3 g / cm 3 , preferably less than 1.2 g / cm 3 By way of example only, calcium aluminate may have a tap density of about 1 g / cm 3 Therefore, the inorganic particles may preferably have a tap density of 0.1 g / cm 3 Up to 1.4g / cm 3 , preferably 0.2g / cm 3 Up to 1.2g / cm 3 The tap density of the silicone resin particles may be 0.3 g / cm 3 Up to 0.9g / cm 3 , preferably 0.5g / cm 3 Up to 0.7g / cm 3 The tap density of the dry particulate composition composed of a mixture of inorganic particles and silicone resin may preferably have the same tap density as described for either the inorganic particles or the silicone resin alone. In some preferred embodiments, the tap density of the dry particulate composition is 0.5 g / cm 3 Up to 1.4g / cm 3 , preferably 0.7 g / cm 3 Up to 1.2g / cm 3 .

[0049] In a preferred embodiment, the spraying step includes a first spraying step in which the inorganic particles are sprayed onto the gas contact surface as a first dry particulate aerosol to form an inorganic particle layer, and then in a second spraying step, the silicone resin is sprayed onto the inorganic particle layer as a second dry particulate aerosol to form the coating. Thus, the inorganic particle layer is sprayed onto the channels of the monolithic article, and then the silicone resin is separately sprayed onto the channels coated with the inorganic particles.

[0050] Even more preferably, the mixture of the inorganic particles and the silicone resin is sprayed onto the gas contact surface as a dry particulate aerosol to form the coating. Thus, the intimate mixture of the inorganic particles and the silicone resin is applied to the gas contact surface of the channel and enhances the adhesion of the inorganic particles to the channel wall when the silicone resin is calcined.

[0051] In the case where a mixture of inorganic particles and silicone resin is sprayed onto a gas contact surface as a dry particulate aerosol to form a coating (preferably, wherein the dry particulate composition consists of inorganic particles and silicone resin), the weight ratio of inorganic particles to silicone resin in the mixture is preferably greater than 0.5 (in other words, greater than 0.5:1), preferably greater than 0.7, preferably greater than 0.9, and / or less than 4, preferably less than 3, preferably less than 2.5. For example, the ratio may preferably be about 1 or about 2. Preferably, the ratio is 0.5 to 4, preferably 0.7 to 3, preferably 0.9 to 2.5, preferably 1 to 2.

[0052] Preferably, the silicone resin has a molecular weight greater than 1,000, preferably greater than 2,000, preferably greater than 5,000, preferably greater than 10,000, and / or a molecular weight less than 500,000, preferably less than 200,000.

[0053] As used herein, molecular weight refers to the weight average molecular weight (M W ), which can be measured using any conventional apparatus in the art. In some embodiments, particularly those embodiments described herein where the silicone resin comprises hydroxyl functional groups, the molecular weight may be relatively low because the hydrogen bonding provided by the hydroxyl functional groups provides the silicone resin with a sufficiently high melting point and / or glass transition temperature. Thus, in some embodiments, the silicone resin may have a molecular weight of 1,000 to 10,000, preferably 1,000 to 5,000, preferably 1,200 to 3,500, such as 1,500 to 2,000. Silicone resins having a molecular weight below 1,000 are less preferred because these silicone resins are generally liquids and are not suitable for dry spraying, or do not have as much branching as larger molecules, which is believed to enhance the bonding of the inorganic particles to the monolithic article.

[0054] However, the molecular weight of the silicone resin may preferably be from 15,000 to 150,000, preferably from 20,000 to 120,000, preferably from 60,000 to 100,000. Some preferred resins have an Mw of 8,000 to 15,000, some from 20,000 to 60,000, and others from 80,000 to 120,000.

[0055] It is particularly preferred that the silicone resin has the formula [R x SiX y O z ] n, where R is an alkyl or aryl group, X is a functional group bonded to silicon, and where z is greater than 1 and less than 2. As will be understood, n is large in order to provide the oligomers or polymers required for silicone resins, especially resins that are solid at room temperature. Although dependent on the molecular weight of the R and X groups, when n is greater than 10, an M greater than 1,000 can be obtained. W , when n is greater than 100, an M greater than 10,000 can be obtained. W , and when n is greater than 1,000, an M greater than 100,000 can be obtained. W . Thus, n can preferably be greater than 10, greater than 100, greater than 1,000.

[0056] As will be understood, R is an alkyl or aryl group bonded to silicon, while X is a non-hydrocarbon functional group bonded to silicon. Similarly, since silicon is a tetravalent atom, it should be understood that x + y + 2z = 4. z is less than 2 because where z = 2, x and y = 0, providing silicon dioxide (i.e., silica; (SiO2) n ). Similarly, z is greater than 1 because where z = 1, x + y = 2, giving a substituted polysiloxane composed of "D" units (e.g., (RXSiO) n ), giving a linear resin (e.g., –O–(SiRX)–O–(SiRX)–O–). An example is polydimethylsiloxane. Thus, O refers to the oxygen that bridges two silicon atoms in the polymer backbone of the silicone resin.

[0057] Preferably, 0 < x + y < 2, preferably 0 < x + y ≤ 1.5, preferably 0 < x + y ≤ 1. Preferably, x, y, and / or x + y are greater than 0.1, preferably greater than 0.2. In a preferred embodiment, x + y is 1, giving a silicone resin commonly referred to as a silsesquioxane. Preferably, y is less than 1 and / or y is less than x. Even more preferably, 2y ≤ x, preferably 5y ≤ x, preferably 10y ≤ x. In one embodiment, y is 0. For example, y is 0 where the silsesquioxane is a polyalkylsilsesquioxane, such as polymethylsilsesquioxane (MeSiO 3 / 2 ) n .

[0058] Typically, when present, X is one or more of H, hydroxyl (OH), Cl and C1-C6 alkoxy, preferably one or more of OH and C1-C6 alkoxy, preferably wherein the C1-C6 alkoxy is selected from methoxy (OCH3) and ethoxy (OCH2CH3). In particularly preferred embodiments, X is one or both of OH and ethoxy. However, X is a functional group, which may also be a reactive functional group such as an amine group (NH2, NR2), an epoxy group, an acrylate group and a vinyl group, but these functional groups are less preferred because the presence of hydroxyl or alkoxy groups is believed to provide more effective crosslinking during calcination. As described above, any oxygen present in the terminal functional group is not effective for the "O" in the above formula. z " has no contribution, the "O z ” refers to silicon bridging oxygen atoms.

[0059] The inventors have found that the silicone resins described herein provide coated monolithic articles with the advantageous benefits of enhanced water resistance and improved thermal stability. It has been found that the silicone resins are particularly advantageous in bonding inorganic particles to the monolithic articles. Without wishing to be bound by theory, the inventors believe that the branched structure and physical properties of the silicone resin allow the resin to first melt in the calcination step as described herein and begin to solidify after bonding (tightly bonding or depositing on) the inorganic particles on the gas contact surface of the channel. As the resin solidifies, the resin forms additional -Si-O-Si-O-Si-bridges / bonds, further increasing its branched structure. In addition, the inventors believe that such bonding may also be formed with the gas contact surface (i.e., the monolithic article itself) and the inorganic particles, for example, by forming -Si-O-Al-bonds, further bonding the particles to the appropriate position in the article. As the temperature continues to increase during calcination, the R and X groups are oxidized, leaving a silica (SiO2) skeleton. Thus, inorganic particles containing silicon and / or aluminum may be preferred, such as zeolites, calcium aluminates, alumina and / or silica.

[0060] Preferably, the silicone resin has a crosslinking degree of greater than 55%, preferably greater than 60%, more preferably greater than 65%, and / or a crosslinking degree of less than 85%, preferably less than 80%.

[0061] As described herein, given the tetravalent nature of silicon, a compound such as x SiX y O z ] nThe silicon atoms of the described silicone resins can be in one of four coordination environments, namely, SiO(R / X)3, SiO2(R / X)2, SiO3(R / X) or SiO4, respectively referred to in the art as "M", "D", "T" and "Q". Thus, the above formula can be described by aMbDcTdQ, where a+b+c+d=1, and the degree of crosslinking is defined by [(a+2b+3c+4d) / 4]*100. The relative ratio of the number of silicon atoms in each coordination environment can be determined using standard spectroscopic techniques (e.g., multinuclear NMR spectroscopy, particularly 29 Si NMR spectroscopy). Alternatively, for commercially available silicone resins, the degree of crosslinking may be provided in the technical data sheet.

[0062] In other words, silicon dioxide (SiO2) is formed entirely of "Q" SiO4 units, in which each silicon atom is bonded to four connected oxygen atoms. Thus, in the case where d is 1, this gives silicon dioxide a 100% degree of crosslinking. On the other hand, by way of example, PDMS is formed entirely of "D" Si(Me)2O2. Thus, in the case where b is 1, this gives polydimethylsiloxane a 50% degree of crosslinking. Thus, the silicone resin preferably has a degree of crosslinking between these two extremes and includes a mixture of such units. Thus, the silicone resin may preferably consist of MDT units, MTQ units, DTQ units or DT units.

[0063] Preferably, R is one or more of a C1-C6 alkyl or a phenyl group. Due to the oligomeric or polymeric nature of the silicone resin, the number of monomer units is generally large. There may be many cases of two groups, R and X, so that the silicone resin described by a single monomer unit may contain a plurality of different groups. As described above with respect to the functional group X, X may preferably be both OH and ethoxy. Similarly, R may include more than one C1-C6 alkyl and / or phenyl group. Therefore, when R is described by more than one group, such as R' and R", the formula of the silicone resin may be [R' x’ R” x” SiX y O z ] n , where x'+x"=x. The same applies to the functional group X.

[0064] Preferably, R is one or more of a straight or branched alkyl group and a phenyl group, one or more of a straight chain alkyl group and a phenyl group, more preferably one or more of a methyl group and a phenyl group. In some preferred embodiments, where R is both a methyl group and a phenyl group, the ratio of phenyl to methyl group is less than 2, preferably less than 1.5, preferably less than 1, preferably less than 0.5. In some embodiments, R is a phenyl group. More preferably, R is a methyl group (i.e., a ratio of 0).

[0065] For the R and X groups, smaller organic groups such as methyl, methoxy and ethoxy are particularly preferred because this increases the SiO2 content of the starting silicone resin, thereby reducing the weight loss during calcination. In addition, the smoke and loss of volatiles (such as H2O, CO2 and other volatile organics) during calcination are reduced.

[0066] Therefore, it is preferred that the silica content of the silicone resin is greater than 50% by weight, preferably greater than 60% by weight, preferably greater than 70% by weight, preferably greater than 80% by weight. The silica content may also be referred to as the ash content, which is the weight of the product (in this case, the product is silica) remaining after complete oxidation, based on the weight of the starting silicone resin. For example, the oxidation may be performed at about 1000°C. Alternatively, the silica content may be obtained from the technical data sheet of a suitable commercially available silicone resin. Alternatively, the silica content may be calculated based on the complete oxidation of silicon to silica and the resin formula. By way of example only, polymethylsilsesquioxane (MeSiO 3 / 2 ) n The silicon dioxide content of polymethylsilsesquioxane is about 2.1*42.7=89.7% by weight (i.e., based on the weight of the silicone resin).

[0067] One particularly preferred silicone resin for use in the process of the present invention is a highly crosslinked ethoxylated poly(dimethylsiloxane) having a silica content of about 82% by weight and a melting point of 35°C to 55°C.

[0068] The method further includes calcining the coating to provide a coated monolithic article.That is, the method includes calcining a porous monolithic article having inorganic particles and a silicone resin sprayed onto the porous monolithic article on gas contacting surfaces of a plurality of channels.

[0069] Preferably, the calcining step comprises heating to a temperature of at least 200° C., preferably at least 300° C., more preferably at least 400° C., and / or to a temperature of at most 600° C., preferably at most 550° C., more preferably at most 530° C. Thus, calcining preferably comprises heating to a temperature of 200° C. to 600° C., preferably 300° C. to 550° C., preferably 400° C. to 530° C., more preferably 400° C. to 500° C., even more preferably 400° C. to 450° C.

[0070] Such temperatures have been found to be most suitable for forming an effective binder that provides advantageous water resistance to the coated monolithic article. Such temperatures are particularly advantageous when the porous monolithic article is a catalyst article, such as a catalytic wall flow filter, because these temperatures allow the silicone resin to be calcined into crosslinked silica without negatively affecting the catalytic efficiency (i.e., without degrading the catalyst article). It is believed that linear siloxanes such as PDMS not only fail to provide the required branching to effectively bind the inorganic particles and adhere to the article, but also require temperatures in excess of 550°C or even 600°C to fully degrade into SiO2. Ideally, the calcination temperature is kept as low as possible to reduce the likelihood of affecting the catalytic activity of any catalyst present in the monolithic article.

[0071] In another aspect of the present invention, there is provided an uncalcined porous monolithic article for forming a monolithic article for treating exhaust gas, the uncalcined porous monolithic article comprising a plurality of channels and comprising a dry particulate composition comprising inorganic particles and a silicone resin, the inorganic particles comprising an aluminosilicate zeolite having a SAR greater than 100:1, the dry particulate composition being located within the channels and / or pores of the uncalcined porous monolith.

[0072] Thus, the uncalcined porous monolith article is suitable for forming a monolith article that can be used for exhaust gas treatment. Preferably, the uncalcined porous monolith article is used to form a monolith article, preferably wherein the monolith article will be used to treat exhaust gas. As described herein with respect to the first aspect, the uncalcined porous monolith article comprises a plurality of channels and comprises a dry particulate composition comprising inorganic particles and a silicone resin, the inorganic particles comprising an aluminosilicate zeolite having a SAR greater than 100:1. The dry particulate composition is located within the channels and / or pores of the uncalcined porous monolith, that is, the composition coats the gas contacting surfaces of the channels.

[0073] Uncalcined porous monolithic articles comprising the dry particulate composition can be formed into monolithic articles by calcining, preferably by heating to the temperatures described herein, to decompose the silicone resin of the dry particulate composition into silica.

[0074] Preferably, the mass loading of the dry particulate composition in the uncalcined porous monolithic article is less than 50 g / L, preferably less than 30 g / L. Preferably, the mass loading of the inorganic particles in the uncalcined porous monolithic article is at least 5 g / L and / or less than 25 g / L. Preferably, the mass loading of the silicone resin in the uncalcined porous monolithic article is at least 5 g / L and / or less than 25 g / L. In a preferred embodiment, the mass loading of the inorganic particles in the uncalcined porous monolithic article is 5 g / L to 15 g / L and / or the mass loading of the silicone resin is 5 g / L to 15 g / L. By way of example, in the case where the weight ratio of inorganic particles to silicone resin is 1:1, the loading of the inorganic particles may be 10 g / L and the loading of the silicone resin may be 10 g / L, so that the total loading of the dry particulate composition is 20 g / L. By way of example, in the case of a 2:1 ratio, the inorganic particle loading may be 10 g / L, while the silicone resin loading is 5 g / L, resulting in a total loading of 15 g / L.

[0075] In a further aspect, there is provided an uncalcined porous monolithic article for forming a monolithic article for treating exhaust gas, the monolithic article being obtainable by a method comprising the steps of:

[0076] providing a porous monolithic article comprising a plurality of channels for passage of exhaust gas, each channel having a gas contacting surface;

[0077] Inorganic particles comprising an aluminosilicate zeolite having a SAR greater than 100:1 and a silicone resin are sprayed onto a gas contacting surface as a dry particulate aerosol to form a coating.

[0078] In another aspect, there is provided a coated monolithic article for treating exhaust gases obtainable by a method as described herein with respect to the first aspect. The coated monolithic article has enhanced water resistance over known coated monolithic articles, and as described herein, the article is preferably a catalytic article and / or a wall flow filter. Such an article is particularly suitable for treating exhaust gases, particularly vehicle exhaust gases. The inventors have found that the highly cross-linked silica present in the coated monolithic article is highly effective in bonding inorganic particles to the gas contacting surfaces of the channels of the porous monolithic article, and the presence of an aluminosilicate zeolite having a SAR greater than 100:1 imparts improved thermal stability to the coated monolithic article.

[0079] In further aspects of the present invention, a vehicle exhaust system including the coated monolithic article is provided.

[0080] Example

[0081] Sample A

[0082] Following the procedure of Example 1 of US20200306692A1, a GPF filter with 75 g / L washcoat loading was prepared from a 300 / 8, 1.3L cordierite substrate.

[0083] Then, zeolite beta powder (SAR=500, d 10 =0.56μm, d 50 =2.6μm, d 90 =37.8 μm) and highly crosslinked ethoxylated poly(dimethylsiloxane) powder (silicon dioxide content 82%, melting point 35°C to 55°C, d 90 =5 μm) was loaded onto the GPF filter. The powder loading before calcination was 4 g / L. The powder mixture was loaded according to the method and apparatus described in WO 2021 / 028692. A downstream regeneration blower was used to blow 550 m 3 / h primary airflow pulls through the filter. A P30 pressure transmitter monitored the back pressure. The refractory powder was dispersed into the primary air stream using a fixed nozzle with a 2 mm fluid cap and a 0.5 mm gap air cap. Compressed air was supplied to the nozzle at 4 bar and positioned 500 mm from the inlet face. The back pressure was used to determine the point at which spraying of the powder mixture was stopped. After loading was completed, the filter was calcined at 530 °C for 35 minutes.

[0084] Comparative Sample B

[0085] Comparative sample B was prepared in the same manner as sample A, except that the latter was loaded with chabazite powder (SAR=20, d 10 =0.73μm, d 50 =2.4μm, d 90 =43.3 μm) and highly crosslinked ethoxylated poly(dimethylsiloxane) powder (silicon dioxide content 82 wt%, melting point 35°C to 55°C, d 90 =5 μm). The powder loading before calcination was 5 g / L.

[0086] Filter test

[0087] The filtration efficiency of the samples was tested on an engine bench on the RDE cycle, fresh and after hydrothermal aging, where the filter samples were subjected to an atmosphere containing 2 wt% oxygen, 10 wt% water, 88 wt% nitrogen at 1050°C for 4 hours. The test results are listed in Table 1. The filtration efficiency in Table 1 is the soot particles removed over the entire driving cycle.

[0088] Table 1

[0089]

[0090] The results show that the reduction in filtration efficiency after aging at 1050°C is much lower for Sample A than for Comparative Sample B.

[0091] In this specification, the term "dry powder" refers to a particulate composition that is not suspended or dissolved in a liquid. This does not necessarily mean the complete absence of all water molecules. Dry powders are preferably free-flowing.

[0092] In this specification, the term "tap density" refers to the tap density of a powder measured according to European Pharmacopoeia 7.0, section 2.9.35, method 1 with 1250 taps.

[0093] In this specification, the term "g / L" (grams per liter) refers to the mass of dry powder divided by the volume of the filter.

[0094] In this specification, the terms "loading" and "mass loading" when referring to the amount of powder refer to the mass of powder added to the filter and can be measured by weighing the filter before and after applying the powder to the filter.

[0095] In this specification, the term " 50 (by volume)" refers to the Malvern Panalytical with Aero s dispersion unit available from Malvern Panalytical Ltd., Malvern, UK. 3000 measured d 50 (by volume) Measurement results. Dispersion conditions: gas pressure = 2 barg, feed rate = 65%, hopper gap = 1.2 mm. Refractive index and absorption parameters according to Malvern 3000 User Manual.

[0096] As used herein, the singular forms "a", "an", and "the" include plural references unless the context clearly indicates otherwise. The use of the term "comprising" is intended to be interpreted as including such features but not excluding other features, and is also intended to include feature options that must be limited to those described. In other words, the term also includes the limitations "essentially consisting of..." (intended to indicate that certain additional components may be present, provided that they do not substantially affect the basic characteristics of the described features) and "consisting of..." (intended to indicate that other features may not be included, so that if these components are expressed in percentages of their proportions, these will add up to 100%, taking into account any unavoidable impurities), unless the context clearly indicates otherwise.

[0097] The foregoing detailed description has been provided by way of explanation and illustration and is not intended to limit the scope of the appended claims. Many variations of the presently preferred embodiments shown herein will be apparent to those of ordinary skill in the art and remain within the scope of the appended claims and their equivalents.

Claims

1. A method for forming an inorganic oxide coating on a monolithic article for treating exhaust gas, the method comprising: providing a porous monolithic article comprising a plurality of channels for passage of exhaust gas, each channel having a gas contacting surface; spraying inorganic particles comprising an aluminosilicate zeolite having a silica to alumina molar ratio (SAR) greater than 100:1 and a silicone resin as a dry particulate aerosol onto a gas contacting surface to form a coating; as well as The coating is calcined to provide a coated monolithic article.

2. The process according to claim 1, wherein the aluminosilicate zeolite has a SAR greater than 200:1, preferably greater than 300:1, more preferably greater than 400:

1.

3. The method of claim 1, wherein the aluminosilicate zeolite is selected from the group consisting of AEI, BEA, CHA and MFI.

4. The method according to claim 1, wherein the monolithic article is a monolithic filter, preferably a wall flow filter, and / or a catalyst article, preferably a catalytic wall flow filter.

5. A method according to any preceding claim, wherein: (i) spraying the inorganic particles as a first dry particle aerosol onto the gas contact surface to form an inorganic particle layer, and then spraying the silicone resin as a second dry particle aerosol onto the inorganic particle layer to form the coating; or (ii) spraying a mixture of the inorganic particles and the silicone resin onto the gas contacting surface as a dry particulate aerosol to form the coating.

6. A method according to any preceding claim, wherein the silicone resin has a molecular weight greater than 1,000, preferably greater than 2,000, preferably greater than 5,000, preferably greater than 10,000, and / or a molecular weight less than 500,000, preferably less than 200,000.

7. The method according to any preceding claim, wherein the silicone resin has a glass transition temperature (Tg) greater than 30°C, preferably greater than 35°C, and / or less than 100°C, preferably less than 80°C.

8. A method according to any preceding claim, wherein the silicone resin has the formula [R x SiX y O z ] n , wherein R is an alkyl group or an aryl group, X is a functional group bonded to silicon, and wherein z is greater than 1 and less than 2.

9. The method of claim 8, wherein y is less than 1, and / or wherein y is less than x.

10. The method according to claim 8 or claim 9, wherein the silicone resin has a crosslinking degree greater than 55%, preferably greater than 60%, more preferably greater than 65%, and / or a crosslinking degree less than 85%, preferably less than 80%.

11. The method according to any one of claims 8 to 10, wherein R is one or more of a C1-C6 alkyl group and a phenyl group, preferably one or more of a straight-chain alkyl group and a phenyl group, preferably one or both of a methyl group and a phenyl group, more preferably a methyl group.

12. The method according to any one of claims 8 to 11, wherein X is one or more of H, OH, Cl and C1-C6 alkoxy, preferably one or more of OH and C1-C6 alkoxy, more preferably one or both of OH and ethoxy.

13. A method according to any preceding claim, wherein the silicone resin has a silica content of greater than 50 wt%, preferably greater than 60 wt%, preferably greater than 70 wt%, preferably greater than 80 wt%.

14. A method according to any preceding claim, wherein the aluminosilicate zeolite is present in the inorganic particles in an amount of 10 to 99 wt%, preferably in an amount of 50 to 99 wt%, more preferably in an amount of 80 to 99 wt%, and most preferably in an amount of 90 to 99 wt%.

15. A method according to any preceding claim, wherein the inorganic particles have a d value greater than 0.2 μm and / or less than 50 μm, preferably less than 25 μm, by volume. 50 .

16. A method according to any preceding claim, wherein calcining comprises heating to a temperature of at least 200°C, preferably at least 300°C, more preferably at least 400°C, and / or a temperature of at most 600°C, preferably at most 550°C, more preferably at most 530°C.

17. A method according to any preceding claim, wherein the monolithic article comprises one or more platinum group metals.

18. A method according to any preceding claim, wherein the dry particulate aerosol is composed of a tap density of less than 1.5 g / cm 3 A dry microparticle composition is formed.

19. A method according to any preceding claim, wherein a mixture of the inorganic particles and the silicone resin is sprayed onto the gas contacting surface as a dry particulate aerosol to form the coating, and wherein in the mixture, the weight ratio of inorganic particles to silicone resin is greater than 0.5, preferably greater than 0.7, preferably greater than 0.9, and / or less than 4, preferably less than 3, preferably less than 2.

5.

20. An uncalcined porous monolithic article for forming a monolithic article for treating exhaust gas, the uncalcined porous monolithic article comprising a plurality of channels and comprising a dry particulate composition comprising inorganic particles and a silicone resin, the inorganic particles comprising an aluminosilicate zeolite having a SAR greater than 100:1, the dry particulate composition being located within the channels and / or pores of the uncalcined porous monolith.

21. The uncalcined porous monolithic article of claim 20, wherein the mass loading of the dry particulate composition is less than 50 g / L, preferably less than 30 g / L.

22. An uncalcined porous monolithic article for forming a monolithic article for treating exhaust gas, the monolithic article being obtainable by a method comprising the steps of: providing a porous monolithic article comprising a plurality of channels for passage of exhaust gas, each channel having a gas contacting surface; Inorganic particles comprising an aluminosilicate zeolite having a SAR greater than 100:1 and a silicone resin are sprayed onto a gas contacting surface as a dry particulate aerosol to form a coating.

23. A coated monolithic article for treating exhaust gases, said coated monolithic article being obtainable by the method according to any one of claims 1 to 19.

24. A vehicle exhaust system comprising the coated monolithic article according to claim 23.

Citation Information

Patent Citations

  • Catalyst article and the use thereof for filtering fine particles

    US20200306692A1

  • Asymmetric honeycomb wall-flow filter having improved structural strength

    WO2005030365A1

  • Diesel particulate filter

    WO2011151711A1

  • Honeycomb body with porous material

    WO2020047708A1

  • Particulate filters

    WO2021028692A1